Mengenal Posisi Marketing Associate Dalam Dunia Digital Marketing - Sofyan Mufti Prasetiyo; Ahmad Firmansyah; Mohamad Sopiyan; Fachrul Abizar (CV. Multi Kreasi Media, 2022)
The world of marketing has recently become the target of job seekers in Indonesia. A wide scope of work with many fields and different team concentrations, makes the field of marketing open up many opportunities and job vacancies. The world of marketing requires experienced people because they deal directly with clients. So marketing companies usually don't want to play around with potential applicants. Marketing associate is an entry-level job so it is perfect for someone who just wants to start working in marketing or marketing. This position works by assisting seniors with the planning and execution of all forms of marketing activities within a company. Marketing associates also help carry out the daily work of seniors so that there is a smooth flow of marketing work.